Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(25\cdot\left(-\frac{1}{3}\right)^3+\frac{1}{5}-2\cdot\left(-\frac{1}{2}\right)^2-\frac{1}{2}\)
\(=25\cdot\frac{-1}{27}+\frac{1}{5}-2\cdot\frac{\left(-1\right)^2}{2^2}-\frac{1}{2}\)
\(=\frac{-25}{27}+\frac{1}{5}-2\cdot\frac{1}{4}-\frac{1}{2}\)
\(=\frac{-98}{135}-\frac{1}{2}-\frac{1}{2}=\frac{-233}{135}\)
\(\left(-2\right)\left(\frac{3}{4}-0,25\right):\left(2\frac{1}{4}-1\frac{1}{6}\right)\)
\(=\left(-2\right)\left(\frac{3}{4}-\frac{25}{100}\right):\left(\frac{9}{4}-\frac{7}{6}\right)\)
\(=\left(-2\right)\left(\frac{75}{100}-\frac{25}{100}\right):\left(\frac{27}{12}-\frac{14}{12}\right)\)
\(=\left(-2\right)\cdot\frac{50}{100}:\frac{13}{12}\)
\(=\left(-2\right)\cdot\frac{1}{2}:\frac{13}{12}\)
\(=-1\cdot\frac{12}{13}=-\frac{12}{13}\)
Ta có: \(4\frac{3}{5}:\frac{2}{3}+1\frac{1}{5}:\frac{2}{5}\)
\(=\frac{12}{5}.\frac{3}{2}+\frac{6}{5}.\frac{5}{2}\)
\(=\frac{18}{5}+3\)
\(=6,6\)
Vậy..........
\(4\frac{3}{5}:\frac{2}{3}+1\frac{1}{5}:\frac{2}{5}\)
= \(\frac{23}{5}:\frac{2}{3}+\frac{6}{5}:\frac{2}{5}\)
= \(\frac{23}{5}x\frac{3}{2}+\frac{6}{5}x\frac{5}{2}\)
= \(\frac{69}{10}+\frac{30}{10}\)
\(=\frac{99}{10}\)
Ta lần lượt có:
\(\dfrac{1}{0,25}=\dfrac{100}{25}=4;\) \(\left(1\dfrac{1}{4}\right)^2=\left(\dfrac{5}{4}\right)^2=\dfrac{25}{16};\)
\(\dfrac{1}{\left(\dfrac{4}{3}\right)^2}=\dfrac{1}{\dfrac{16}{9}}=\dfrac{9}{16};\) \(\left(\dfrac{5}{4}\right)^3=\dfrac{125}{64}\) và \(\dfrac{1}{\left(-\dfrac{2}{3}\right)^3}=\dfrac{1}{-\dfrac{8}{27}}=-\dfrac{27}{8}\)
Vậy \(P=4.\dfrac{25}{16}+25.\left[\dfrac{9}{16}:\dfrac{125}{64}\right]:\left(-\dfrac{27}{8}\right)\)
\(=\dfrac{25}{4}-25.\dfrac{9}{16}.\dfrac{64}{125}.\dfrac{8}{27}\)
\(=\dfrac{25}{4}-\dfrac{32}{15}\)
\(=\dfrac{375-128}{60}=\dfrac{247}{60}\)
P=4.(25/16)+25.(9/16:25/16):(-27/8)
=25/4 +25.(9/25):(-27/8)
=25/4 +9:(-27/8)
=25/4 +(-8/3)
=43/12
1)
a. \(\left(3x^2-50\right)^2=5^4\)
\(\Leftrightarrow3x^4-50=625\)
\(\Leftrightarrow3x^4=675\)
\(\Leftrightarrow x^4=225\)
\(\Leftrightarrow x=\sqrt{15}\)
2)
a. \(\frac{\left(3^4-3^3\right)^4}{27^3}=\frac{3^{16}-3^{12}}{\left(3^3\right)^3}=\frac{3^{12}.3^4-3^{12}}{3^9}=\frac{3^{12}\left(3^4-1\right)}{3^9}\)
\(=\frac{3^{12}.80}{3^9}=3^3.80=27.80=2160\)
b. \(\frac{25^3}{\left(5^5-5^3\right)^2}=\frac{\left(5^2\right)^3}{5^{10}-5^6}=\frac{5^6}{5^6.5^4-5^6}=\frac{5^6}{5^6\left(5^4-1\right)}\)
\(=\frac{5^6}{5^6.624}=\frac{1}{624}\)
\(a,\left(\frac{3}{8}+-\frac{3}{4}+\frac{7}{12}\right):\frac{5}{6}+\frac{1}{2}\)
= \(\left(-\frac{3}{8}+\frac{7}{12}\right):\frac{5}{6}+\frac{1}{2}\)
= \(\frac{5}{24}:\frac{5}{6}+\frac{1}{2}\)
= \(\frac{1}{4}+\frac{1}{2}\)
= \(\frac{3}{4}\)
b)\(-\frac{7}{3}.\frac{5}{9}+\frac{4}{9}.\left(-\frac{3}{7}\right)+\frac{17}{7}\)
=\(-\frac{35}{27}+\left(-\frac{4}{21}\right)+\frac{17}{7}\)
= \(-\frac{35}{27}+\frac{47}{21}\)
= \(\frac{178}{189}\)
c) \(\frac{117}{13}-\left(\frac{2}{5}+\frac{57}{13}\right)\)
= \(\frac{117}{13}-\frac{311}{65}\)
= \(\frac{274}{65}\)
d) \(\frac{2}{3}-0,25:\frac{3}{4}+\frac{5}{8}.4\)
= \(\frac{2}{3}-\frac{1}{4}:\frac{3}{4}+\frac{5}{8}.4\)
= \(\frac{2}{3}-\frac{1}{3}+\frac{5}{2}\)
= \(\frac{1}{3}+\frac{5}{2}\)
= \(\frac{17}{6}\)
\(25\%-1=\dfrac{1}{4}-1=\dfrac{1-4}{4}=-\dfrac{3}{4}\\ \\= \dfrac{1}{2}-\dfrac{1}{4}+\dfrac{1}{4}:1=\dfrac{1}{2}-\dfrac{1}{4}+\dfrac{4}{1}=\dfrac{2-1+16}{4}=\dfrac{1}{2}\)